The effect of in silico targeting Pseudomonas aeruginosa patatin-like protein D, for immunogenic administration. (June 2018) - Chirani, Alireza Salimi; Majidzadeh, Robabeh; Pouriran, Ramin; Heidary, Mohsen; Nasiri, Mohammad Javad; Gholami, Mehrdad; Goudarzi, Mehdi; Omrani, Vahid Fallah
Graphical abstract: Abstract: The vaccine candidates that have been introduced for immunization against Pseudomonas aeruginosa ( P. aeruginosa ) strains are quite diverse. In fact, there has been no proper antigen to act as an effective immunogenic substance against this ubiquitous pathogen in the market as yet. The complications caused by this bacterium due to the rapid development of multiple drug resistant strains have led to clinical problems worldwide. P. aeruginosa encodes many specific virulence elements that could be used as appropriate vaccine candidates. Type Vd secretion system, also known as patatin-like protein D, is a novel P. aeruginosa auto-transporter system. It is known that cellular or humoral immune responses could be elevated by chimeric proteins carrying epitopes. It has been recognized that in silico tools are essential for the evaluation of new chimeric antigens. In this study, we have considered the patatin-like protein D (PlpD) molecule from P. aeruginosa and predicted some immunogenic properties of this strong cytotoxic phospholipase A2 with the use of in-depth computational and immunoinformatics assessment methods The novelty of our in silico study is the modeling and assessment of both humoral and cellular immune potential against the PlpD molecule. The molecule was considered by multiple sequence alignment and homology valuation. The extremely conserved regions in the PlpD were predicted. The allergenic and physicochemical property predictions on the PlpD state that the molecule is a non-allergic and stable molecule. High-resolution secondary and tertiary conformations were created. Indeed, the B-cell and T-cell epitope mapping on the chimeric target protein confirmed that the engineered protein contained a tremendous number of both B-cell and T-cell corresponding epitopes. This investigation magnificently attained the chimeric molecule as being a potent lipolytic enzyme composed of numerous B-cell and T-cell restricted epitopes and could induce both humoral and cellular immune responses. The results indicated that this molecule has therapeutic potential against several potent pathogenic P. aeruginosa strains.